2012
DOI: 10.1016/j.electacta.2011.11.028
|View full text |Cite
|
Sign up to set email alerts
|

Polyvinylpyrrolidone assisted sol–gel route LiCo1/3Mn1/3Ni1/3PO4 composite cathode for aqueous rechargeable battery

Abstract: Kandhasamy, S., Pandey, A. and Minakshi, M. (2012)Polyvinylpyrrolidone assisted sol-gel route LiCo1/3Mn1/3Ni1/3PO4 composite cathode for aqueous rechargeable battery. Electrochimica Acta, 60 (15 Jan This is a PDF file of an unedited manuscript that has been accepted for publication. As a service to our customers we are providing this early version of the manuscript. The manuscript will undergo copyediting, typesetting, and review of the resulting proof before it is published in its final form. Please note that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 55 publications
(30 citation statements)
references
References 39 publications
1
29
0
Order By: Relevance
“…Also, Sasaki et al [25] reported that the trapped organic between electrode-electrolyte interface increase the lithium ion diffusion rate with better capacity retention. The direct evidences of trapped polymer layer formations in PVP are reported by the authors in a separate publication [26]. On the other hand, chelating agents CA (from 40 to 30 mAh/g) and TEA (from 68 to 38 mAh/g) cathodes showed drastic loss of 23 % and 45 % in their capacities respectively on subsequent cycles.…”
Section: Electrochemical Characterization Of Lico 1/3 Mn 1/3 Ni 1/3 Pmentioning
confidence: 83%
“…Also, Sasaki et al [25] reported that the trapped organic between electrode-electrolyte interface increase the lithium ion diffusion rate with better capacity retention. The direct evidences of trapped polymer layer formations in PVP are reported by the authors in a separate publication [26]. On the other hand, chelating agents CA (from 40 to 30 mAh/g) and TEA (from 68 to 38 mAh/g) cathodes showed drastic loss of 23 % and 45 % in their capacities respectively on subsequent cycles.…”
Section: Electrochemical Characterization Of Lico 1/3 Mn 1/3 Ni 1/3 Pmentioning
confidence: 83%
“…To investigate the role of synthesis in forming structural defects, we synthesized our cathode (LiCo 1/3 Ni 1/3 Mn 1/3 PO 4 ) by sol-gel synthesis using different chelating agents. The x-ray diffraction patterns (XRD) of triethanolamine (TEA) and polyvinylpyrrolidone (PVP) [36] assisted sol-gel synthesized materials are shown in Fig. 4.…”
Section: (C) Role Of Defects and Synthesis Conditionsmentioning
confidence: 99%
“…All the samples presented a relatively dense structure (free from voids) though some micro-structural differences can be identified. It is reported earlier [23] that the solid state synthesized sample is not homogenous with irregular particle sizes and well separated grains compared to that of wet chemistry route (presented here). The sol-gel product (Fig.…”
Section: Resultsmentioning
confidence: 94%